Strategy Planning Based on Factors Affecting Behavior of Healthy Food Consumption - Vanya Permata Azzura; Muslim, Erlinda (Jurnal Sistem Teknik Industri, 2023)
Healthy food is a basic human need that needs to be fulfilled every day. Eating healthy food is an effort to maintain a healthy body. In fact, many people still have a poor eating diet. Poor eating diet can cause a non-contagious disease. The high number of patients that suffer with diseases will be a burden for both the community and the state. This is because a non-contagious disease is a disease that is not contagious but has a high risk of death. A non-contagious disease patient will take a long time to be healed and the medication itself cost a lot of money. To maintain a healthy body consumption of healthy food is important, especially for people of Jakarta that have a poor eating diet. This study was conducted to identify the factors that influence the habit of eating healthy foods using an extended model of Theory of Planned behavior (TPB) by adding the factors of Health Consciousness and Knowledge of Healthy Food. Analysis of the mediation and moderation effect of the factors was carried out using Structural Equation Modeling (SEM). After gaining the result from the analysis, this study will create a strategy based on it and prioritized them using the Relationship Matrix.